AYURVEDIC MANAGEMENT OF INFERTILITY DUE TO TUBAL BLOCKAGE- A CASE STUDY (International Journal of Ayurveda and Pharma Research, 2021)
Infertility is defined as failure to conceive within one or more years of regular unprotected coitus. Tubal blockage is one of the most common causative factors for female infertility. The prevalence of fallopian tubal obstruction was 19.1% in the fertility age group. In this case study patient suffered from infertility since 3yrs and diagnosed as primary infertility due to right tubal blockage after allopathic consultation. IUI has done thrice which went unsuccessful and was advised for IVF. But she was reluctant to do the same. So she approached OPD of GAVCH for W&C, Poojappura, Kerala for Ayurvedic management. Patient was managed with Ayurvedic treatment protocol including internal medications and purification therapies. The line of treatment was to normalize the Vata-kapha dosha and removes the Sroto avarodha in the fallopian tube. Uttaravasti delivers medicines close to Garbhashaya & Yoni especially in fallopian tubes. Taila can help to clear the Sroto rodha due to its Vyavayi, Vikashi and Sookshma property. Just after one cycle of treatment patient came with positive urine pregnancy test after one week of missed period. Then she took regular antenatal care from an allopathic hospital and delivered a healthy male baby of 2.8 kg.